(untitled) (International Journal of Current Engineering and Technology, 2014)
A smart mechatronic system was developed in this work to control a Spark Ignition, SI, engines. A self-regulative control system was proposed to run the engine at the optimum thermal efficiency whatever the loading value is. An experimental test rig was developed to apply and verify the present control system. The test rig consists of a speed sensing, engine loading, and air and fuel metering hardware modules. A software program was developed by the authors to control the engine speed very near to the design speed value, while applying the best economy air to fuel, A/F, ratio on the engine. Off-line and on-line self regulation techniques were developed, and implemented by the control soft ware to decide the air and fuel rates corresponding to the optimum efficiency. The speed signal and the fuel and air control commands are exchanged via an I/O digital data acquisition card, DAQ, connected to a host personal computer. Off-line self regulation technique is faster but needs updating from time to time due to the engine ageing. The on-line technique is always up to date but takes a relatively long time to decide the best A/F ratio. Experimental results showed that, the present smart control system improves the thermal efficiency in a range from 8 to 10% compared to the stochiometric engine operation.